2006
DOI: 10.1038/sj.bjp.0706856
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cardamonin on lipopolysaccharide‐induced inflammatory protein production and MAP kinase and NFκB signalling pathways in monocytes/macrophages

Abstract: Background and purpose: In this study we examined the effect of the natural product cardamonin, upon lipopolysaccharide (LPS)-induced inflammatory gene expression in order to attempt to pinpoint the mechanism of action. Experimental approaches: Cardamonin was isolated from the Greek plant A. absinthium L. Its effects were assessed on LPSinduced nitrite release and iNOS and COX-2 protein expression in two macrophage cell lines. Western blotting was used to investigate its effects on phosphorylation of the mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 47 publications
1
76
0
3
Order By: Relevance
“…Chalcones are naturally occurring compounds belonging to the flavonoid family and exhibiting a broad spectrum of biological activities, including anti-cancer, anti-inflammatory, anti-oxidative, anti-viral, anti-fungal, and anti-allergic activities (12). Cardamonin (2=,4=-dihydroxy-6=-methoxychalcone) is a chalcone mainly existed in the seeds of Alpinia Katsumadai Hayata, a plant that has been widely used in oriental medicine to treat emesis and gastric disorders (20).…”
mentioning
confidence: 99%
“…Chalcones are naturally occurring compounds belonging to the flavonoid family and exhibiting a broad spectrum of biological activities, including anti-cancer, anti-inflammatory, anti-oxidative, anti-viral, anti-fungal, and anti-allergic activities (12). Cardamonin (2=,4=-dihydroxy-6=-methoxychalcone) is a chalcone mainly existed in the seeds of Alpinia Katsumadai Hayata, a plant that has been widely used in oriental medicine to treat emesis and gastric disorders (20).…”
mentioning
confidence: 99%
“…NF-jB activation and related iNOS production in LPS-stimulated cells were inhibited by a direct effect on the capacity of the transcription factor to bind DNA [50]. Interestingly, Israf et al [60] reported inhibition of COX-2 and iNOS expression by cardamonin (22) via dose-dependent suppression of IjBa phosphorylation and degradation in LPS-induced RAW 264.7 macrophages, clearly describing a cell-type-specific effect of this compound.…”
Section: Inflammation Cell-signaling Pathways Targeted By Chalconesmentioning
confidence: 95%
“…3 Cardamonin's name comes from the fact that it can be found in cardamom spice (Fig. 4), but since the first article where it was described, 22 it has been found in many other (some of them edible) plant species, such as Alpinia blepharocalyx, 23,24 Alpinia gagnepainii, 25 Alpinia conchigera, 26,27 Alpinia hainanensis, [28][29][30][31][32][33][34][35][36][37][38][39][40] Alpinia malaccensis, 41 Alpinia mutica, 42,43 Alpinia pricei, 44 Alpinia rafflesiana, [45][46][47][48] Alpinia speciosa, 22,49,50 Amomum subulatum, 51 Artemisia absinthium, 52 Boesenbergia pandurata, [53][54][55][56][57][58][59][60] Boesenbergia rotunda, 61,62 Carya cathayensis, 63 Cedrelopsis grevei, 64 Combretum apiculatum, 65 Comptonia pere...…”
Section: Sources Of Cardamoninmentioning
confidence: 99%
“…Anti-inflammatory, antineoplastic, and antioxidant activity Several authors 26,36,46,52,81 have aimed to explain the antiinflammatory activity of cardamonin by fully observing its influence over the signaling pathway of the nuclear factorjB (NF-jB)-a protein complex that controls transcription of DNA and plays a crucial role in regulating immune responses to infection 1,82 -and detail the mechanism of action on the lipopolysaccharide (LPS)-induced inflammatory gene expression. A 27% inhibition of LPS-induced NO production with a 1 lM can be found in literature.…”
Section: Health Applicationsmentioning
confidence: 99%